Watching, Waiting (Leuven University Press, 2023)
First study on empty places in photography and the Covid-19 pandemic. In the aftermath of Covid-19, the subject of ‘empty places’ has gained renewed topicality and resonance. Watching, Waiting presents a collection of essays that brings emptiness into interdisciplinary focus as an object of study that extends beyond the present. The contributors approach the specific interrelationships of photography and place through emptiness by considering historical and contemporary material in equal measure. Drawing on architecture, anthropology, sociology, and public health, among other fields, they provide insights into geographically and temporally diverse production models of empty places and their corresponding complex and sensitive global and local relations, while also tackling the ethics of behaviour and protests that unfold within them. The book's chapters, both photographic and scholarly essays, cover areas that range widely both thematically and geographically, spanning static film footage of Nicosia's Buffer Zone, protest photographs in the wake of the Black Lives Matter movement in Bristol, staged images from the University of Zagreb's ethnological archives, historic landscape and architectural photography, aerial shots of Covid-19 mass graves in Brazil, photos of artificially built field hospitals and quarantine rooms during the pandemic, and images of empty airports at night. Through still and moving images, Watching, Waiting examines the photographic aestheticisation of emptiness, existing stereotypes of ‘empty places’, and transformations of human experiences.